2016
DOI: 10.1158/1538-7445.sabcs15-p6-12-09
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-12-09: Uptake of genetic testing for BRCA mutations in a medically underserved population

Abstract: Introduction: Genetic testing for hereditary cancer syndromes is recommended in specific populations to identify individuals at increased risk for developing malignancies. The uptake of genetic testing for BRCA mutations in studies has ranged from 44%-81% but has not been well studied in medically underserved populations. In this study we identified factors that predicted uptake of genetic testing among a medically underserved population undergoing genetic counseling in the Cancer Risk Program a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have shown that women of color and lower income women have less knowledge of and limited access to cancer genetic counseling (GC) and genetic testing (GT) (Walcott et al 2014;Mai et al 2014;Cragun et al 2015). Even where these services are available, uptake may be low compared with white and higher income populations (Sheppard et al 2013;Butrick et al 2015;Gaber et al 2016). While the Affordable Care Act of 2010 and lower costs of testing have made hereditary cancer services more accessible for low-income individuals in recent years (FORCE 2015), access alone may not be sufficient to ensure high quality GC and appropriate testing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that women of color and lower income women have less knowledge of and limited access to cancer genetic counseling (GC) and genetic testing (GT) (Walcott et al 2014;Mai et al 2014;Cragun et al 2015). Even where these services are available, uptake may be low compared with white and higher income populations (Sheppard et al 2013;Butrick et al 2015;Gaber et al 2016). While the Affordable Care Act of 2010 and lower costs of testing have made hereditary cancer services more accessible for low-income individuals in recent years (FORCE 2015), access alone may not be sufficient to ensure high quality GC and appropriate testing.…”
Section: Introductionmentioning
confidence: 99%